2019
DOI: 10.1016/j.trim.2019.101213
|View full text |Cite
|
Sign up to set email alerts
|

Banff lesions and renal allograft survival in chronic-active antibody mediated rejection

Abstract: Aims: Chronic-active antibody mediated rejection (c-aABMR) is a major cause of kidney graft loss. Currently, little is known about the relation between histopathologic parameters and renal allograft survival. Methods and results: Between 2008 and 2014, 41 patients with a progressive decrease in renal function were diagnosed with c-aABMR according to Banff 2015 and followed up for at least 3 years. Clinical and renal biopsy characteristics were analyzed for association with graft survival. During follow-up 26 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Before 2009, donor-speci c anti-HLA antibodies (DSA) were not routinely assessed in the period of data collection but 40% of the tested cases (N=70) were DSA positive. When histologic criteria were met, a diagnosis of c-aABMRh, termed suspicious for c-aABMR in the Banff 2015 criteria, was made in accordance with recent publications 13,14,[31][32][33] .…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Before 2009, donor-speci c anti-HLA antibodies (DSA) were not routinely assessed in the period of data collection but 40% of the tested cases (N=70) were DSA positive. When histologic criteria were met, a diagnosis of c-aABMRh, termed suspicious for c-aABMR in the Banff 2015 criteria, was made in accordance with recent publications 13,14,[31][32][33] .…”
Section: Study Populationmentioning
confidence: 99%
“…After diagnosis of c-aABMR progression to renal allograft failure and response to therapy is highly variable and not readily explained by clinical characteristics and Banff scores [13][14][15] . In addition, some patients have only subclinical c-aABMR, which is only detected by a protocol biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…However, we require more additional data and experiments to verify this hypothesis. Intimal arteritis caused by vascular rejection has previously considered to be a feature of acute cellular rejection (1,27). In the revised 2013 Banff criteria, vascular arteritis (v > 0) was included in the diagnostic criteria for active antibody-mediated rejection (19).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic active antibody-mediated rejection (CAAMR) is an intermediate process that occurs during the development of chronic antibody-mediated rejection (CAMR), which has been recognized recently. CAAMR leads to the gradual loss of allograft, becoming an obstacle to the long-term survival of renal allografts ( 1 ). Significant improvements in short-term renal graft survival have been achieved in recent decades due to the continuous updating of immunosuppressive agents, such as calcineurin inhibitors, which greatly reduce the occurrence of T cell-mediated rejection (TCMR) ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Banff 2015 classification suggested that pathological chronic injury and evidence of antibody interaction on the microvascular endothelium or evidence of DSA, but not both, was suspicious lesion of CAABMR [9]. In a recent study, the Banff acute and chronic pathological scores showed no difference between DSA-positive and -negative (suspicious for CAABMR in Banff 2015 classification) groups [10]. We recently defined biopsy-proven acute/active ABMR regardless of DSA positivity as "pathological" acute/active ABMR, and the acute and chronic Banff scores showed no significant difference among groups with pathological acute/ active ABMR with different levels of DSA mean fluorescence intensity [11].…”
Section: Introductionmentioning
confidence: 98%